A Novel Combined Tumor Budding-Poorly Differentiated Clusters Grading System Predicts Recurrence and Survival in Stage I-III Colorectal Cancer. (25th October 2022) - Shivji, Sameer; Cyr, David P.; Pun, Cherry; Duan, Kai; Sari, Aysegul; Tomin, Rossi; Ng, Deanna; Brar, Amanpreet; Zerhouni, Siham; Kennedy, Erin; Brar, Mantaj; Swallow, Carol J.; et al.
Abstract : Tumor budding (TB) and poorly differentiated clusters (PDCs) are powerful prognostic factors in colorectal cancer (CRC). Despite their morphologic and biological overlap, TB and PDC are assessed separately and are distinguished by an arbitrary cutoff for cell cluster size. This cutoff can be challenging to apply in practice and its biological significance remains unclear. We developed a novel scoring system that incorporates TB and PDC into a single parameter ("Combined Score"; CS), eliminating the need for such cutoffs and allowing the prognostic value of PDC to be captured alongside TB. In a cohort of 481 stage I-III CRC resections, CS was significantly associated with American Joint Committee on Cancer (AJCC) stage, T-stage, N-stage, histologic grade, tumor deposits, lymphovascular invasion, and perineural invasion ( P <0.0001). In addition, CS was significantly associated with decreased 5-year recurrence-free survival, overall survival, and disease-specific survival ( P <0.0001). TB and PDC showed similar associations with oncologic outcomes, with hazard ratios consistently lower than for CS. The association between CS and oncologic outcomes remained significant in subgroup analyses stratified by AJCC stage, anatomic location (rectum/colon) and neoadjuvant therapy status. On multivariable analysis, CS retained its significant association with oncologic outcomes ( P =0.0002, 0.005, and 0.009) for recurrence-free survival, disease-specific survival, and overall survival, respectively. In conclusion, CS provides powerful risk stratification in CRC which is at least equivalent to that of TB and PDC assessed individually. If validated elsewhere, CS has practical advantages and a biological rationale that may make it an attractive alternative to assessing these features separately.